2021
DOI: 10.1002/ajcp.12496
|View full text |Cite
|
Sign up to set email alerts
|

Relating through Oppression: Longitudinal Relations between Parental Racial Socialization, School Racial Climate, Oppressed Minority Ideology, and Empathy in Black Male Adolescents’ Prosocial Development

Abstract: This research explored whether Black male adolescents’ (N = 453; Mage = 13.72, SD = 1.33) perceptions of parental racial socialization (i.e., behavioral racial socialization) and school racial climate (i.e., equitable school racial climate) were associated with prosocial outcomes (i.e., prosocial behaviors and positive relations with others) across three waves of adolescence. This study also explored whether youth’s beliefs about the extent to which Black individuals and other marginalized communities are unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
(90 reference statements)
0
15
0
Order By: Relevance
“…One longitudinal study of Black adolescents found that perceived parental racial socialization (a combination of racial pride and preparation for bias) at 10th grade (on average 16 years old) predicted increases in adolescents’ beliefs at 12th grade about the academic achievement gap as resulting from structural challenges rather than innate capabilities (Bañales et al, 2020). With the same sample, they also found that parents’ higher frequency of engaging in racial socialization activities was positively related to Black male adolescents’ willingness to be in solidarity with other ethnic minority groups and take collective actions against discrimination after 1 year (Bañales et al, 2021). The findings show the potential of parental ethnic–racial socialization to contribute to adolescents’ resistance against structural inequities.…”
Section: Families In Marginalized Positions: the Critical Role Of Eth...mentioning
confidence: 90%
“…One longitudinal study of Black adolescents found that perceived parental racial socialization (a combination of racial pride and preparation for bias) at 10th grade (on average 16 years old) predicted increases in adolescents’ beliefs at 12th grade about the academic achievement gap as resulting from structural challenges rather than innate capabilities (Bañales et al, 2020). With the same sample, they also found that parents’ higher frequency of engaging in racial socialization activities was positively related to Black male adolescents’ willingness to be in solidarity with other ethnic minority groups and take collective actions against discrimination after 1 year (Bañales et al, 2021). The findings show the potential of parental ethnic–racial socialization to contribute to adolescents’ resistance against structural inequities.…”
Section: Families In Marginalized Positions: the Critical Role Of Eth...mentioning
confidence: 90%
“…A critical analysis of racism is predicated on youth’s racism awareness, or the ability to recognize race‐related phenomena, issues, or disparities in society, the country, and the world (Hope et al., 2015; Rowley et al., 2008). Racism operates on interpersonal, cultural, institutional, and structural levels (Jones, 1983; Neblett, 2019), and youth may learn to recognize these levels of racism throughout adolescence (Bañales, Aldana, et al., 2021, Bañales, Lozada, et al., 2021; Constante et al., 2021; Richards‐Schuster & Aldana, 2013). Interpersonal racism involves people’s endorsement of stereotypes, prejudice, and involvement in verbal and physical forms of racial discrimination (Bonilla‐Silva, 2017; Jones, 1997; Tatum, 2017).…”
Section: Critical Analysis Of Racism: a Key Ingredientmentioning
confidence: 99%
“…This suggests that youth who adopt a sense of a minoritized identity may see their experiences of oppression as linked with other similarly marginalized groups raising their awareness of systemic inequality and fueling their desire to address these inequities. A recent study of Black male adolescents found that those who were able to relate to other marginalized communities through a shared experience of oppression were more likely to feel empathy towards others’ lived experiences, and these feelings served as an indirect pathway to engage in more prosocial behaviors and relate positively with others (Bañales et al, 2021). Collectively, this work highlights the potential for cross-racial coalition building as a response to the shared experiences of racial discrimination groups of color face.…”
Section: What Develops?mentioning
confidence: 99%
“…It seems likely that individuals’ racial or cultural ideologies—that is, beliefs about how people in one’s racial or cultural group should behave and what they should value relative to other groups (Sellers et al, 1998)—may also inform their capacity to disrupt racism, their own or that experienced by others. For instance, having a stronger oppressed minority ideology (i.e., people of different ethnic-racial groups experience and should work together to combat marginalization and discrimination, without necessarily equating those experiences) was associated with greater empathy, and in turn, more prosocial behaviors among Black male youth (Bañales et al, 2021). Although the authors did not examine this, it may be the case that endorsing an oppressed minority ideology may promote cross-racial empathy with other racially marginalized groups as well; this could serve as an important foundation for cross-racial coalition work.…”
Section: What Develops?mentioning
confidence: 99%